Malignant glioma in L-2-Hydroxy Glutaric Aciduria: thorough molecular characterization of a case and literature review - Cordier, Fleur; Wesseling, Pieter; Tops, Bastiaan B.J.; Kester, Lennart; French, Pim J.; van den Bent, Martin; Hinz, Felix; Aronica, Eleonora; Slot, K. Mariam; Abbink, Floor; van der Knaap, Marjo S.; Kranendonk, Mariëtte E.G. (Free Neuropathology, 2024)
L-2-hydroxyglutaric aciduria (L-2-HGA) is a rare neurometabolic disorder characterized by accumulation of L2-hydroxyglutarate (L-2-HG) due to mutations in the L2HGDH gene. L-2-HGA patients have a significantly increased lifetime risk of central nervous system (CNS) tumors. Here, we present a 16-year-old girl with L-2-HGA who developed a tumor in the right cerebral hemisphere, which was discovered after left-sided neurological deficits of the patient. Histologically, the tumor had a high-grade diffuse glioma phenotype. DNA sequencing revealed the inactivating homozygous germline L2HGDH mutation as well as inactivating mutations in TP53, BCOR and NF1. Genome-wide DNA-methylation analysis was unable to classify the tumor with high confidence. More detailed analysis revealed that this tumor clustered amongst IDH-wildtype gliomas by methylation profiling and did not show the glioma CpG island methylator phenotype (G-CIMP) in contrast to IDH-mutant diffuse gliomas with accumulated levels of D-2-HG, the stereoisomer of L-2-HD. These findings were against all our expectations given the inhibitory potential of 2-HG on DNA-demethylation enzymes. Our final integrated histomolecular diagnosis of the tumor was diffuse pediatric-type high-grade glioma, H3-wildtype and IDH-wildtype. Due to rapid tumor progression the patient died nine months after initial diagnosis. In this manuscript, we provide extensive molecular characterization of the tumor as well as a literature review focusing on oncogenetic considerations of L-2-HGA-associated CNS tumors.